COVID-19 exposure and depression-anxiety levels among Saudi adults in the Jazan region: a study with a predominantly female and undergraduate sample - Busili, Amani; Makrami, Azizah; Keni, Amnah; Khardily, Alaa; Alzahrani, Dalyah; Busaily, Idris; Busayli, Fatimah (Frontiers in Psychiatry, 2023)
Background The COVID-19 pandemic has caused significant mental health challenges worldwide, as evidenced by numerous studies indicating high levels of depression and anxiety among individuals. However, the extent of mental health disorders following the pandemic and the association between anxiety and depression and COVID-19 exposure levels in the Jazan region of the Kingdom of Saudi Arabia have received little research attention. Methods A convenience sample of 377 participants, predominantly female (85.4%) with undergraduate education (74.5%) and Saudi nationality (92.8%), was included in the study. The study utilized a self-administered questionnaire to collect data from participants between 1st August and 8th September 2022. The questionnaire consisted of four parts, including demographic characteristics, COVID-19 exposure, the Patient Health Questionnaire-9 (PHQ-9) for depression assessment, and the Generalized Anxiety Disorders-7 (GAD-7) for anxiety evaluation. Statistical techniques such as descriptive statistics, independent t-tests, ANOVA (Analysis of Variance), and regression analysis were employed to analyze the collected data. Results The mean age of the study participants was 30.97 years (SD = 9.072). The mean score for COVID-19 exposure was 2.98 (SD = 1.48). The mean level of depression was 7.83 (SD = 6.43), with 20% of participants experiencing moderate to severe depression. Additionally, the study found that the mean score of anxiety level among participants was 6.75 (SD = 6.57), with 26% of the participants experiencing moderate to severe anxiety. Independent t-test revealed significant differences in mean depression and anxiety scores between participants with varying COVID-19 exposure levels (p = 0.001). The regression analysis demonstrated that anxiety levels were significant predictors of depression (p < 0.001). There is a significant difference in the depression mean between participants with high levels of anxiety (≥10) compared to others with levels <10. Furthermore, significant predictors of anxiety levels included either student or unemployment status (p < 0.001), increased age (≥35) (p = 0.049), female gender (p = 0.009), marital status of not being married, divorced, or widowed (p = 0.004), low monthly income (p = 0.019), and increased depression level (p < 0.001). Conclusion This study provides evidence of significant depression and anxiety levels among participants, with higher COVID-19 infection exposure correlating with increased scores for both. Anxiety was identified as a significant predictor of depression. Demographic factors, such as employment status, age, gender, and marital status, played a role in influencing anxiety levels. The findings highlight the need for targeted mental health interventions to address the psychological impact of COVID-19 infection exposure and support affected individuals effectively.